2009
DOI: 10.1007/s11101-009-9152-6
|View full text |Cite
|
Sign up to set email alerts
|

Mallotus species from Vietnamese mountainous areas: phytochemistry and pharmacological activities

Abstract: The genus Mallotus belongs to Malphighiales order and Euphorbiaceae family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 81 publications
(121 reference statements)
0
33
0
Order By: Relevance
“…DPPH • has an absorption band at 515 nm, which disappears upon reduction by an antiradical compound. The assay was carried out (11,12,19,22,27,29,32). The regression coefficients from PLS and O-PLS models, preprocessed with normalization and column centering, are also given.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…DPPH • has an absorption band at 515 nm, which disappears upon reduction by an antiradical compound. The assay was carried out (11,12,19,22,27,29,32). The regression coefficients from PLS and O-PLS models, preprocessed with normalization and column centering, are also given.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…For instance, the genus Mallotus has been used for the treatment of chronic hepatitis and enteritis [17,18], while the genus Phyllanthus has been used for kidney, urinary bladder, and intestinal infections, and for diabetes [19,20]. Recently, many studies were performed concerning the chemical components of Mallotus and Phyllanthus species and several pharmacologically active constituents were determined [12,[21][22][23][24][25]. Cytotoxic (Mallotus apelta [22]), antimicrobial (Mallotus peltalus [22], Phyllanthus emblica [24]), anti-inflammatory (Mallotus peltalus [22], Mallotus spodocarpys [22]), and antioxidant activities (Mallotus metcalfianus [23], Phyllanthus emblica [21], Phyllanthus niruri [25]) have been reported for both genera.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pharmaceutical research has found that some of chemical constituents of Mallotus have the capability to possess several biological activities such as antioxidant, anti-inflammatory, antimicrobial, antiviral, cytotoxic and antitumor activities [3]. Therefore, the outcomes from this study will improve and enhance the application of natural product in the development of drug discovery.…”
Section: -2506mentioning
confidence: 82%
“…Mallotus is a genus of shrubs, trees and climbers with approximately 150 species were distributed in tropical and sub-tropical regions of Asia [2]. The genus of Mallotus belongs to the Malphighiales order, the Euphorbiaceae family, Acalyphoideae subfamily, Acalypeae pro parte and Rotterinae subtribe [3]. Research on Mallotus species revealed that this genus were very rich with active…”
Section: Introductionmentioning
confidence: 99%
“…The genus comprises over 140 species of which many are used as traditional medicines in Asia [20]. Over the years, the genus has provided scientists a broad basis in their research for new pharmacological compounds.…”
Section: Introductionmentioning
confidence: 99%